Investment Project Analysis Of Extra Facility Business Model Case Study: Pt. Pln (Persero) Riau And Riau Islands Distribution Units - Silvia Iriani; S. K. Wiryono (Al-Makki Publisher, 2023)
The development of disruptive business and technology has the potential to reduce the growth of electricity sales. The existence of